The biochemistry of headgroup exchange during triacylglycerol synthesis in canola. (19th February 2020) - Bai, Shuangyi; Wallis, James G.; Denolf, Peter; Engelen, Steven; Bengtsson, Jesse D.; Van Thournout, Michel; Dierickx, Jo; Haesendonckx, Boris; Browse, John
SUMMARY: Many pathways of primary metabolism are substantially conserved within and across plant families. However, significant differences in organization and fluxes through a reaction network may occur, even between plants in closely related genera. Assessing and understanding these differences is key to appreciating metabolic diversity, and to attempts to engineer plant metabolism for higher crop yields and desired product profiles. To better understand lipid metabolism and seed oil synthesis in canola ( Brassica napus ), we have characterized four canola homologues of the Arabidopsis ( Arabidopsis thaliana ) ROD1 gene. AtROD1 encodes phosphatidylcholine:diacylglycerol cholinephosphotransferase (PDCT), the enzyme that catalyzes a major flux of polyunsaturated fatty acids (PUFAs) in oil synthesis. Assays in yeast indicated that only two of the canola genes, BnROD1.A3 and BnROD1.C3, encode active isozymes of PDCT, and these genes are strongly expressed during the period of seed oil synthesis. Loss of expression of BnROD1.A3 and BnROD1.C3 in a double mutant, or by RNA interference, reduced the PUFA content of the oil to 26.6% compared with 32.5% in the wild type. These results indicate that ROD1 isozymes in canola are responsible for less than 20% of the PUFAs that accumulate in the seed oil compared with 40% in Arabidopsis. Our results demonstrate the care needed when translating results from a model species to crop plants. Significance Statement: Relative to the model oilseed Arabidopsis, the canola phosphatidylcholine:diacylglycerol cholinephosphotransferase has a lesser role in the flux of fatty acids during seed oil synthesis, highlighting how pathway fluxes may differ among related species.